Application of singlet sink approach for matrix-free amorphous photon upconversion films. (October 2021) - Raišys, Steponas; Adomėnienė, Ona; Adomėnas, Povilas; Juršėnas, Saulius; Kazlauskas, Karolis
Abstract: Recently introduced singlet exciton sink approach for sensitized photon upconversion (UC) systems was shown to suppress undesired back-transfer of the upconverted singlets from an emitter to a sensitizer by trapping them at highly emissive sink sites, thus enabling to boost UC efficiency. Here we report on the successful application of this approach to matrix-free amorphous UC films based on bisfluorene-anthracene (BFA) emitters and platinum octaethylporphyrin (PtOEP) sensitizer. The approach enabled to roughly double UC efficiency in one of the BFA/PtOEP films owing to effective Förster resonant energy transfer (FRET) from BFA to the sink. Although a highly efficient FRET (amounting to 88%) was achieved prior to the sink aggregation, the relatively large sink concentration triggered unwanted FRET from the sink to the sensitizer, thus adversely affecting the UC performance of the system. Nevertheless, the maximum UC quantum yield attained for the amorphous BFA/PtOEP films (ΦUC = 3.4%) compares favorably with leading literature values for the solid state UC systems. The obtained results revealed an additional constraint for the singlet sink, i.e., the necessity to achieve maximal FRET at the low sink concentration to reduce the probability for harmful sink aggregation as well as unwanted energy transfer from the sink to the sensitizer. Highlights: Singlet exciton sink approach boosts TTA-UC efficiency of matrix-free films. Suppression of the back-FRET {emitter→sensitizer} doubles UC efficiency. Maximal UC quantum yield achieved in solid bisfluorene-anthracene films is 3.4%. Maximal FRETemitter→sink at the lowest possible sink concentration is critical.